2008
DOI: 10.1089/neu.2007.0441
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Bax Protein Prevents Neuronal Cell Death but Produces Cognitive Impairment in Mice following Traumatic Brain Injury

Abstract: Apoptosis contributes to delayed neuronal cell death in traumatic brain injury (TBI). To investigate if Bax plays a role in neuronal cell death and functional outcome after TBI, Bax gene disrupted (null) mice and wild type (WT) controls were subjected to the controlled cortical impact (CCI) model of TBI. Motor function in WT and Bax null mice was evaluated using the round beam balance and the wire grip test on days 0–5. Spatial memory was assessed using a Morris Water Maze adopted for mice on days 14–18 post i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…Mechanical disruption of neurons triggers a cascade of events leading to neuronal cell death following TBI (2). Apoptosis has been attributed to programmed neuronal cell death in TBI (3). Notably, previous studies have also shown that autophagy is increased following TBI (4).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical disruption of neurons triggers a cascade of events leading to neuronal cell death following TBI (2). Apoptosis has been attributed to programmed neuronal cell death in TBI (3). Notably, previous studies have also shown that autophagy is increased following TBI (4).…”
Section: Introductionmentioning
confidence: 99%
“…We noted a spectrum of functional deficits rarely seen when CCI is studied alone (Abrahamson et al, 2009;Smith et al, 1995;Tehranian et al, 2006Tehranian et al, ,2008Whalen et al, 1999aWhalen et al, ,1999bYou et al, 2008). We chose a mild to moderate CCI to limit functional deficits and neuropathology due to CCI alone, so that the full impact of secondary HS could be revealed.…”
mentioning
confidence: 99%
“…Unlike the Bid-/-and previous Bax-/-studies, injuryinduced caspase-3 expression within the cortex or hippocampus did not differ between Bax null and wild-type mice, although Bax null mice did not exhibit the post-traumatic nuclear translocation of activated caspase-3 observed in wild-type mice. Despite a reduction in numbers of TUNEL+ cells with apoptotic morphology within the dentate gyrus and CA1 regions of the hippocampus 24 h after CCI, only small, nonsignificant decreases in cortical lesion size or CA1 and CA3 neuronal death were noted [38]. Importantly, uninjured Bax null mice had significantly larger brain size and CA1 neuronal cell numbers compared to wild-type mice, consistent with abnormal developmental pruning through apoptosis.…”
Section: Bcl-2 Family (Bid Bax)mentioning
confidence: 85%
“…AIF0apoptosis-inducing factor; CypA0cyclophilin A; DFF=DNA fragmentation factor; PARP0poly(ADPribose) polymerase mice [37]. A second study sought to confirm acute changes in cell survival after CCI injury in Bax null mice [38]. Unlike the Bid-/-and previous Bax-/-studies, injuryinduced caspase-3 expression within the cortex or hippocampus did not differ between Bax null and wild-type mice, although Bax null mice did not exhibit the post-traumatic nuclear translocation of activated caspase-3 observed in wild-type mice.…”
Section: Bcl-2 Family (Bid Bax)mentioning
confidence: 99%
See 1 more Smart Citation